EKSPLOITASI ANAK PADA KELUARGA MISKIN DI KELURAHAN TONA I KECAMATAN TAHUNA TIMUR KABUPATEN KEPULAUAN SANGIHE - Tumengkol, Meivy R (HOLISTIK, Journal Of Social and Culture, 2016)
Children at has been less got any attention from parents so bad for his future because children no understand of their rights their own. Children to lack of attention from the parent so bad for his future. Children are unable to enjoy his time to learn and play in school. Children who actually whose main duty was to learn at school to get the science, but employed by his parents to helping in the field, this initiative was one of an example of the exploitation of children carried out by the parents. Exploitation against children of the poor families in Kelurahan Tona I caused by poverty prolonged so the head family taking any shortcut in a way that is a piece of to improve economic conditions family. Exploitation against children never have a bad impact to the son, because it was after undergo the process of exploitation it turns out that the child can receive these facts and remain undergo this until they think are enough to attend the normal life as anyone else. Keywords: children, exploitation, family